“Taking a Half Day at a Time:” Patient Perspectives and the HIV Engagement in Care Continuum - Christopoulos, Katerina A. (Mary Ann Liebert, Inc., 2013)
The HIV treatment continuum, or “cascade,” outlines key benchmarks in the successful treatment of HIV-infected individuals. However, the cascade fails to capture important dimensions of the patient experience in that it has been constructed from a provider point of view. In order to understand meaningful steps in the HIV care cascade for individuals diagnosed with HIV through expanded, more routine testing, we conducted in-depth interviews (n=34) with three groups of individuals: those diagnosed with HIV in the emergency department/urgent care clinic who linked to HIV care and exhibited 100% appointment adherence in the first 6 months of HIV care; those diagnosed in the emergency department/urgent care clinic who linked to HIV care and exhibited sporadic appointment adherence in the first 6 months of HIV care, and; hospitalized patients with no outpatient HIV care for at least 6 months. This last group was chosen to supplement data from in-care patients. The engagement in care process was defined by a changing perspective on HIV, one's HIV identity, and the role of health care. The linkage to care experience laid the groundwork for subsequent retention. Interventions to support engagement in care should acknowledge that patient concerns change over time and focus on promoting shifts in perspective.